2016
DOI: 10.1021/acs.jpcc.6b07930
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Hydride- to Siloxane-Terminated Silicon Quantum Dots

Abstract: Peripheral surface functionalization of hydrideterminated silicon quantum dots (SiQD) is necessary in order to minimize their oxidation/aggregation and allow for solution processability. Historically thermal hydrosilylation addition of alkenes and alkynes across the Si−H surface to form Si−C bonds has been the primary method to achieve this. Here we demonstrate a mild alternative approach to functionalize hydride-terminated SiQDs using bulky silanols in the presence of free-radical initiators to form stable si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Surface oxidation can reduce the QY, but oxidation does not necessarily lead to low PL efficiency. For example, Si nanocrystals embedded in SiO 2 substrates made by ion implantation followed with thermal annealing have exhibited bright PL, , and nanocrystals linked to capping ligands by Si–O and Si–S bonds have also exhibited bright PL with quantum yield similar to alkyl-passivated (Si–C) nanocrystals. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface oxidation can reduce the QY, but oxidation does not necessarily lead to low PL efficiency. For example, Si nanocrystals embedded in SiO 2 substrates made by ion implantation followed with thermal annealing have exhibited bright PL, , and nanocrystals linked to capping ligands by Si–O and Si–S bonds have also exhibited bright PL with quantum yield similar to alkyl-passivated (Si–C) nanocrystals. ,, …”
Section: Resultsmentioning
confidence: 99%
“…For example, Si nanocrystals embedded in SiO 2 substrates made by ion implantation followed with thermal annealing have exhibited bright PL, 46,47 and nanocrystals linked to capping ligands by Si−O and Si−S bonds have also exhibited bright PL with quantum yield similar to alkyl-passivated (Si−C) nanocrystals. 9,43,48 For the very small nanocrystals, there is an increasing probability that the exciton will interact with the nanocrystal surface and nonradiative channels such as defects on the surface or vibrational modes of the capping ligands. 49 The probability of finding an exciton outside the nanocrystal depends on its wave function Ψ, which is obtained by solving the timeindependent Schrodinger equation:…”
Section: = +mentioning
confidence: 99%
“…Michalska reported that homogeneous and silica-supported rhodium­(I) complexes might be used for the reaction of several silanols with a series of various hydrosilanes . Anderson et al described a direct conversion of hydride-terminated silicon quantum dots mediated by radical initiators . Recently, the Shimada group has reported a pioneering work on the selective synthesis of hydro-substituted siloxanes and SQs by Au-catalyzed dehydrogenative cross-coupling reaction of hydrosilanes with compounds containing silanol groups .…”
Section: Introductionmentioning
confidence: 99%
“…38 Anderson et al described a direct conversion of hydride-terminated silicon quantum dots mediated by radical initiators. 39 Recently, the Shimada group has reported a pioneering work on the selective synthesis of hydro-substituted siloxanes and SQs by Au-catalyzed dehydrogenative cross-coupling reaction of hydrosilanes with compounds containing silanol groups. 40 Also worthy of note is the comprehensive use of B(C 6 F 5 ) 3 as the catalyst in the processes utilizing silanols 41,42 and alkoxysilanes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Fortunately, due to the several silicon sources and rich groups on the surface, silicon quantum dots (SiQDs) present colorful luminescent and absorbent properties by adjusting the groups on SiQDs surface so that they can emit light from blue to red. Based on their luminescent properties, many applications are possible, such as photostable biological probes, light-emitting diode, alkaline phosphatase detection, etc. But there are no studies on the detailed absorption properties of water-soluble SiQDs with low cost, especially UV absorption and related applications, and their UV absorption mechanism has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%